Penerapan Sistem Suplai Air Terintegrasi untuk Budidaya Bioflok Nila dan Greenhouse Sayur di KWT Mandiri Batu (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The Kelompok Wanita Tani (KWT) Mandiri in Mojorejo Hamlet, Batu City, manages Nile tilapia biofloc culture and vegetable production in a greenhouse, but water delivery had relied on a manually moved hose. This community service program aimed to install an integrated water supply system linking a storage tank, booster pump, main pipeline, biofloc pond outlet, and greenhouse distribution line. The activity used technical assistance and technology transfer through field observation, hydraulic design, component selection, pipe fabrication, installation, functional testing, and operational guidance. The installed system successfully conveyed water from the storage tank through the pump and pipeline to the biofloc pond outlet, while the greenhouse distribution line was arranged along the planting beds. Visual testing showed a continuous water flow and confirmed the functional connection among the main components. The system simplified pond filling, organized the distribution network, and reduced the need to move hoses repeatedly. However, performance evaluation remained qualitative because pressure, discharge, head loss, and irrigation uniformity were not measured using gauges or flow meters. Therefore, follow-up monitoring is required to quantify hydraulic performance and optimize irrigation scheduling. The program demonstrates that a simple, maintainable water-supply network can support more practical management of integrated aquaculture and greenhouse activities at the community level.